Oxalamide-based bisdiamidophosphites: synthesis, coordination, and application in asymmetric metallocatalysis. Issue 10 (5th April 2019) - Gavrilov, Konstantin N.; Mikhel, Igor S.; Zheglov, Sergey V.; Gavrilov, Vladislav K.; Chuchelkin, Ilya V.; Firsin, Ilya D.; Birin, Kirill P.; Pytskii, Ivan S.; Paseshnichenko, Ksenia A.; Tafeenko, Victor A.; Chernyshev, Vladimir V.; Shiryaev, Alexei A.
Abstract : A new group of P *-chiral bisdiamidophosphites has been developed for Pd- and Rh-catalyzed asymmetric reactions with good to excellent enantioselectivities. Abstract : A series of easy-to-prepare and modular chiral bisdiamidophosphites with oxalamide linkers were synthesized. The structures of the novel ligands were elucidated by means of 2D-NMR and confirmed by single-crystal X-ray diffraction. The reactions of such ligands with [Pd(Cod)Cl2 ] at molar ratios of L/Pd = 1 and 0.5 were studied by 1 H, 13 C, 13 C DEPT, 31 P, 1 H– 13 C HSQC, 1 H– 13 C HMBC, 1 H– 1 H COSY, 1 H– 1 H ROESY, 1 H– 15 N HMBC and DOSY spectroscopy, as well as by DFT calculations. Stereoselectors of this type exhibited high enantioselectivities in the Pd-catalyzed allylic substitution reactions of ( E )-1, 3-diphenylallyl acetate with p TolSO2 Na (up to 92% ee), CH2 (CO2 Me)2 (up to 97% ee), (CH2 )4 NH (up to 96% ee), (EtO)2 P(O)CH2 NH2 (up to 96% ee) and (CH2 )4 N(CCH(CH2 )4 ) (up to 92% ee). ee values of up to 90%, 97% and 83% were obtained in the Pd-mediated allylic alkylation of cinnamyl acetate with ethyl 2-oxocyclohexane-1-carboxylate, allylic amination of cyclohex-2-en-1-yl ethyl carbonate with dibenzylamine and desymmetrization of N, N' -ditosyl- meso -cyclopent-4-ene-1, 3-diol biscarbamate, respectively. In addition, ee values of up to >99% were achieved in the Rh-catalyzed asymmetric hydrogenation of methyl esters of unsaturated acids.